2016
DOI: 10.1007/s00464-016-4941-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative ultrasound-guided transversus abdominis plane block on pain after laparoscopic surgery for colorectal cancer: a double-blind randomized controlled trial

Abstract: In colorectal cancer patients undergoing laparoscopic colorectal surgery, a TAP block did not offer enough benefit for clinical efficacy in terms of postoperative pain or analgesic consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 17 publications
0
58
1
Order By: Relevance
“…1; see www.karger.com/doi/10.1159/000487323 for all online suppl. material) [2,[9][10][11][12][13][14]. The characteristics of the included studies are shown in online supplementary Table 1.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…1; see www.karger.com/doi/10.1159/000487323 for all online suppl. material) [2,[9][10][11][12][13][14]. The characteristics of the included studies are shown in online supplementary Table 1.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
“…Sample sizes ranged from 40 to 147 patients. Among the included studies, 5 reported that TAP block was performed after the induction of anesthesia [2,10,[12][13][14], and 2 studies reported that TAP block was conducted at the end of surgery [9,11]. In addition, ultrasound-guided TAP block was conducted in 5 trials, and conventional TAP block was performed in 2 [9,11].…”
Section: Description Of Included Trialsmentioning
confidence: 99%
See 3 more Smart Citations